1984
DOI: 10.1139/b84-065
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the giant cells induced by Meloidogyne javanica in lima bean

Abstract: Giant cells associated with egg-laying females of Meloidogyne javanica in lima bean, Phaseolus lunatus cv. L-136, were examined by light and electron microscopy. These giant cells have characteristics that are typical of nematode-induced giant cells in a wide range of hosts, but they differ in that they (i) are less closely associated with xylem vessels, (ii) contain a very large number of plastids which are devoid of starch grains, and (iii) contain several different forms of cytoplasmic crystals. One form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…However, these bodies were larger than OPs. Fattah and Webster (1984) illustrated in nematodeinfected plants paracrystalloid bodies similar to those described here. They suggested that these bodies could have corresponded to protein crystals formed by cuboid subunits.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, these bodies were larger than OPs. Fattah and Webster (1984) illustrated in nematodeinfected plants paracrystalloid bodies similar to those described here. They suggested that these bodies could have corresponded to protein crystals formed by cuboid subunits.…”
Section: Discussionsupporting
confidence: 74%
“…Unbound crystalline bodies have likewise been illustrated from plants infected by viruses, for example in oats infected with the blue dwarf virus (Zeyen and Banttari 1972), solely insect-transmitted, or by other pathogens (Fattah and Webster 1984;Sanger et al 1998). The 28-30 nm virus particles forming the crystalline bodies described by Zeyen and Banttari (1972) were equally numerous in phloem cells, even intermixed with degraded host tissue, and in this respect may show features analogous to those described here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation